To study the role of brand loyalty on Gen-Z’s buying behaviour of mobile phones in Ahmedabad city. - Yashvi Bhatt (Journal of Advanced Research in Service Management, 2025)
The current study investigates the relationship between consumer brand loyalty for mobile phones and demographic characteristics, specifically age. A structured questionnaire was administered to 150 respondents, and the data were analysed using SPSS software, including frequency distributions, reliability tests, and chi-square association tests. The 11 items assessing brand loyalty demonstrated strong internal consistency, as indicated by a Cronbach’s Alpha value of 0.817. The majority of respondents were male (60%), between the ages of 18 and 25 (50%), and graduates (51.3%), according to the frequency analysis. To investigate the relationship between age and different aspects of brand loyalty, crosstab and chi-square analyses were carried out. Age and (i) faith in the quality of the favored brand (p = 0.014), (ii) the impact of positive reviews and word-of-mouth on loyalty (p = 0.018), and (iii) hesitancy to move to another brand (p = 0.007) were shown to be strongly correlated. According to these results, older consumers exhibit more consistent loyalty patterns, whereas younger consumers are more impacted by peer ratings and have an emotional bond with reputable companies. Age did not significantly correlate with other criteria like price sensitivity, after-sales service, or social media influence. The study’s findings highlight the necessity for marketers to adjust their branding and communication methods in accordance with demographic profiles, even while brand loyalty is present across age groups and its determinants differ with age.